Prawa majątkowe do świadectw pochodzenia energii ze źródeł odnawialnych jako towarowy instrument pochodny - Borys, Grażyna (Property rights for energy form renewable sources certificates as a derivative commercial instrument, 2007)
The objective of the hereby article becomes the mechanism of property rights turnover regarding certificates for energy originating from renewable sources included into commercial derivative instruments. The objective for such mechanism implementation is to promote and develop production in such renewable sources. The composite elements of this mechanism become the system of establishing and registering certificates for renewable energy origins as well as the system of stock exchange turnover regarding property rights for energy origin certificates. Both of these components are extensively characterized and evaluated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 9-17